A recent dispersal event from the southern Arabian Peninsula resulted in a new subspecies of Helianthemum (Cistaceae) in Western India - Patel, Rohitkumar M.; Prajapati, Sujitkumar R.; Gosavi, Kumar Vinod Chhotupuri; Valerio-Arana, María; Albaladejo, Rafael G.; Martín-Hernanz, Sara; Aparicio, Abelardo (Phytotaxa, 2026)
Indian populations of Helianthemum (Cistaceae), previously identified as H. lippii, are re-evaluated here using an integrative approach combining morphology, molecular systematics based on plastid (ndhF, psbA-trnH, trnL-trnF) and nuclear (ITS) DNA sequences, and cytogenetic data. The morphological traits and phylogenetic results suggest a close relationship with a Helianthemum lineage from the southern Arabian Peninsula and the Horn of Africa, particularly with H. citrinum. The Indian plants are described here as H. citrinum subsp. kachchhicum. The phylogenetic reconstructions provided evidence that this subspecies likely originated from a recent dispersal event from the southern Arabian Peninsula around 120,000 years ago. Overall, this study carries significant biogeographical and evolutionary implications and highlights the limited understanding of Helianthemum beyond its Mediterranean biodiversity hotspot.